(untitled) (European Journal of Health Research, 2021)
The interpersonal difficulties of university students may affect their academic performance. Regarding students who manifest perfectionist automatic thoughts, they tend to show difficulties in heterosexual relationships. This research aimed to examine the relationship and predictive capacity of constructs related to perfectionism on difficulties in relationships with people of the opposite sex. 1298 Ecuadorian university students were recruited. 51.8% of the sample were men (n = 672). The Perfectionism Cognition Inventory and the Cuestionario de Evaluación de Dificultades Interpersonales en la Adolescencia were answered by the participants. Statistically significant differences were found in the different variables of perfectionistic automatic thoughts (i.e., Perfectionist Concerns, Perfectionist Demands, and Perfectionist Efforts) according to high and low levels of difficulties in heterosexual relationships. It was also found that the variable Perfectionist Efforts is a negative and significant predictor of high difficulties in heterosexual relationships. However, the variables Perfectionist Concerns and Perfectionist Demands are a positive and significant predictor of high levels in this type of interpersonal difficulties. All these results confirm that perfectionist automatic thoughts are related and are predictors of difficulties that Ecuadorian university students manifest in their heterosexual relationships.